"Compensations of poverty" : la féerie urbaine ou la modernité en question dans "On Third Avenue" et "Ephemerid" de Mina Loy - Laure De Nervaux-Gavoty (Anglophonia)
This paper explores the poetics of metamorphosis in "On Third Avenue" and "Ephemerid" by Mina Loy. Her ambivalent response to modernity comes to the fore in the representation of an urban fairyland influenced by the works of Baudelaire, surrealist writers as well as the box constructions of Joseph Cornell. Modernity’s indebtedness to an unacknowledged past is at the heart of the aesthetic experience staged in these two poems.